Surgeons and the Scope - Zetka, James R., 1957- (Book collections on Project MUSE., 2003)
In Surgeons and the Scope, James R. Zetka Jr. describes the impact of the video laparoscope on the work lives of contemporary surgeons. The video laparoscope allows surgeons to peer into the inner abdomen with a miniaturized camera, thereby enabling them to perform complex operations without large incisions through small ports punched into the abdominal wall. This technological innovation revolutionized surgery as we know it. Zetka blends rich interview and archival data into a compelling account of an important technological development. He shows how the new laparoscopic technology challenged surgeons to rethink their approaches to surgery, to relearn basic hand-eye coordination, to master complex machinery, and to shift from individualistic to team-based work strategies. Zetka then explains how and why general surgeons embraced this disruptive technology by examining the breakdown of the division of labor between general surgeons and gastroenterologists in response to the unintended and unanticipated outcomes of the scope technology. In Surgeons and the Scope, Zetka weaves cultural, structural, and political economic developments into a sophisticated account of technological change. By viewing the advent of laparoscopic surgery within the context of the history, culture, and ideology of medicine, Zetka provides a deeper understanding of the politics of technology, particularly its effects on job skills, occupations, and worker control.